Unconventional Superconductors Experimental Investigation of the Order-Parameter Symmetry - Goll, Gernot (Springer Tracts in Modern Physics, 2006)
This book offers a comprehensive summary of experiments that are especially suited to reveal the order-parameter symmetry of unconventional superconductors. It briefly introduces readers to the basic theoretical concepts and terms of unconventional superconductivity, followed by a detailed overview of experimental techniques and results investigating the superconducting energy gap and phase, plus the pairing symmetry. This review includes measurements of specific heat, thermal conductivity, penetration depth and nuclearmagnetic resonance and muon-spin rotation experiments. Further, point-contact and tunnelling spectroscopy and Josephson experiments are addressed. Current understanding is reviewed from the experimental point of view. With an appendix offering five tables with almost 200 references that summarize the present results from ambient pressure heavy-fermion and noncopper-oxide superconductors, the monograph provides a valuable resource for further studies in this field.